Imagining Change: An Integrative Approach toward Explaining the Motivational Role of Mental Imagery in Pro-environmental Behavior - Boomsma, Christine; Pahl, Sabine; Andrade, Jackie (Frontiers in Psychology, 2016)
Climate change and other long-term environmental issues are often perceived as abstract and difficult to imagine. The images a person associates with environmental change, i.e., a person’s environmental mental images, can be influenced by the visual information they come across in the public domain. This paper reviews the literature on this topic across social, environmental, and cognitive psychology, and the wider social sciences; thereby responding to a call for more critical investigations into people’s responses to visual information. By integrating the literature we come to a better understanding of the lack in vivid and concrete environmental mental imagery reported by the public, the link between environmental mental images and goals, and how affectively charged external images could help in making mental imagery less abstract. Preliminary research reports on the development of a new measure of environmental mental imagery and three tests of the relationship between environmental mental imagery, pro-environmental goals and behavior. Furthermore, the paper provides a program of research, drawing upon approaches from different disciplines, to set out the next steps needed to examine how and why we should encourage the public to imagine environmental change.